Psectrascelis senex sp. nov. (Coleoptera: Tenebrionidae), a new species from the southern Atacama Desert, Chile - Villablanca-Miranda, Vicente; Villablanca, Javier; Zúñiga-Reinoso, Álvaro (Zootaxa, 2022)
Psectrascelis Solier, 1836 is the most specious South American genus of Nycteliini, which inhabit arid and semiarid regions. Recent expeditions to the southern part of the Atacama Desert collected specimens of Psectrascelis which do not fit with any other described species belonging to this genus. These specimens are morphologically close to P. penai Kulzer, 1955 but the presence of carinae on the elytra easily differentiates this taxon from this mentioned above. Here, we analyzed external morphology, both male and female genitalia, and sequences from a fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene with that of morphologically close species. Our study supports the description of Psectrascelis senex sp. nov. and suggests that P. senex sp. nov. is the sister species of P. penai.